Factors Influencing Active Participation in the Chronic Disease Management Program (Prolanis) - Cahyaningrum, Ika Cahyaningrum; Rosdiana, Yanti; Pajojang, Arifen Leihu; Erwanto, Erwanto (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Non-communicable diseases, such as hypertension and diabetes mellitus, are major contributors to high morbidity and mortality rates globally. To address this, the government has initiated the Prolanis program for BPJS Health participants, aiming to improve the health status of individuals with chronic diseases. However, preliminary studies involving Prolanis program coordinators at a Puskesmas revealed that the participation rate for medical consultations was below the target of 80%. This study aims to identify the factors influencing the activeness of Prolanis participants. Utilizing a quantitative approach with an analytic observational design, the research employed a cross-sectional method. The study was conducted at a community health center in Malang City from September to November 2023. The population comprised all Prolanis participants in the area, totaling 90 individuals, with a research sample of 73 participants. The sampling technique used was consecutive sampling. The independent variables investigated were education level, duration of illness, quality of service, and family support, while the dependent variable was the activeness of Prolanis participants. Data collection instruments included questionnaires for the independent variables and an observation sheet to measure participant activeness. The data were analyzed using a multivariate logistic regression test. The results indicated that family support and service quality were significantly related to the activeness of Prolanis participants, with p-values of 0.000 for both variables. Family support emerged as the most influential factor, with an odds ratio (OR) of 48.706. The study concludes that family support and the quality of health center services are significantly associated with the activeness of Prolanis participants, whereas education level and duration of illness are not related.